2020
DOI: 10.1093/mnras/staa2192
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the spin-pole orientation, jet morphology, and rotation of interstellar comet 2I/Borisov with deep HST imaging

Abstract: We present high resolution, deep imaging of interstellar comet 2I/Borisov taken with the Hubble Space Telescope/Wide Field Camera 3 (HST/WFC3) on 2019 December 8 UTC and 2020 January 27 UTC (HST GO 16040, PI Bolin) before and after its perihelion passage in combination with HST/WFC3 images taken on 2019 October 12 UTC and 2019 November 16 UTC (HST GO/DD 16009, PI Jewitt) before its outburst and fragmentation of March 2020, thus observing the comet in a relatively undisrupted state. We locate 1-2″ long (2,000 -… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
6
2
Order By: Relevance
“…Rosetta observations of 67P revealed that the peak of water flux was confined to the subsolar latitude either on the northern hemisphere or the southern hemisphere, whereas, the hypervolatile CO 2 and CO gases were not specifically originating from the sunlit regions 34 . Two studies based on the HST observations of 2I/Borisov suggest that the sub-solar latitude of the nucleus evolved either from −35 • to 0 • or from −10 • to 70 • between August 2019 and January 2020 27,48 . The drastic drop in the water production rate of 2I/Borisov may have been due to the possibility that water sublimation was mainly coming from a confined region on the surface of the nucleus.…”
mentioning
confidence: 99%
“…Rosetta observations of 67P revealed that the peak of water flux was confined to the subsolar latitude either on the northern hemisphere or the southern hemisphere, whereas, the hypervolatile CO 2 and CO gases were not specifically originating from the sunlit regions 34 . Two studies based on the HST observations of 2I/Borisov suggest that the sub-solar latitude of the nucleus evolved either from −35 • to 0 • or from −10 • to 70 • between August 2019 and January 2020 27,48 . The drastic drop in the water production rate of 2I/Borisov may have been due to the possibility that water sublimation was mainly coming from a confined region on the surface of the nucleus.…”
mentioning
confidence: 99%
“…On the other hand, the equatorial coordinates of the Sun when 2I/Borisov reached perihelion on December 8, 2019 were approximately (254 • .6, −22 • .7), so none of our predictions are close to the position favored by Sekanina (1981). This location is also inconsistent with the estimates provided by Ye et al (2020), Bolin & Lisse (2020), and Kim et al (2020); it is, however, somewhat consistent with the spin-axis direction computed by Manzini et al (2020). Most of the observed properties of interstellar comet 2I/Borisov have been found to be remarkably similar to those of known Solar System comets (see for example de León et al 2019León et al , 2020Fitzsimmons et al 2019;Opitom et al 2019;Cremonese et al 2020;Guzik et al 2020;Jewitt et al 2020b;Kareta et al 2020;Yang et al 2020).…”
Section: I/borisovmentioning
confidence: 58%
“…Most of the observed properties of interstellar comet 2I/Borisov have been found to be remarkably similar to those of known Solar System comets (see for example de León et al 2019León et al , 2020Fitzsimmons et al 2019;Opitom et al 2019;Cremonese et al 2020;Guzik et al 2020;Jewitt et al 2020b;Kareta et al 2020;Yang et al 2020). Recent estimates, placed the rotation period of 2I/Borisov at about 5.3 h or perhaps 10.6 h (Bolin & Lisse 2020). Gladman et al (2019) had found a very slow rotation rate with a period of about 13 d. If confirmed, this would be the longest rotation period ever observed in a comet.…”
Section: I/borisovmentioning
confidence: 65%
See 1 more Smart Citation
“…It should also be noted that others (e.g., Moreno et al 2019) report no variation in photometry over a time span longer than these periods. This very small amplitude demonstrates the challenge of photometrically extracting a rotation period from an active body (see also Bolin & Lisse 2020, for an example).…”
Section: Introductionmentioning
confidence: 97%